THE IMPORTANCE EMPLOYEE ENGAGEMENT IN MEDIATING PERCEIVED ORGANIZATIONAL SUPPORT ON JOB PERFORMANCE - Hasani, Syaiful; Churiyah, Madziatul (Nusantara Economics and Entrepreneurships Journals, 2024)
Employee engagement mediates work performance and perceived organisational support in this study. This study examines how perceived organisational support affects job performance, employee engagement, and job performance in shoe SMEs in East Java, as well as whether employee engagement mediates the relationship between the two. Partial Least Squares regression using SmartPLS version 3.0 showed that perceived organisational support directly affected job performance. This suggests that organisational effectiveness improves with perceived support. Employee involvement indirectly impacts job performance. However, the indirect effect is still smaller than the direct effect of perceived organisational support on job performance, indicating that employee engagement owned by company employees cannot mediate the relationship. To boost employee performance, an organisation must increase perceived organisational support. To test model mediation, review employee involvement. Assessing employee performance and organisational support requires further assessments. Employee engagement can be influenced by internal and external influences, unlike many researches.